Understanding Growth-Induced Trends in Local Climate Zones, Land Surface Temperature, and Extreme Temperature Events in a Rapidly Growing City: A Case of Bulawayo Metropolitan City in Zimbabwe - Mushore, Terence Darlington; Mutanga, Onisimo; Odindi, John (Frontiers in Environmental Science, 2022)
Assessment of the responses of urban thermal environment on climate is important, especially in view of possible influence on low and high temperature extreme events. This study assessed the combination of remotely sensed land surface temperature (LST) and Local Climate Zones (LCZs) with in-situ air temperature-retrieved extreme temperature indices to assess the effect of urban growth on the three dimensional thermal environment in Bulawayo metropolitan city, Zimbabwe. LST and LCZ were derived from Landsat data for 1990, 2005 and 2020, while extreme temperature indices as well as their trends were derived from daily minimum and maximum temperature data from a local weather station. Results showed that built LCZ expanded at the expense of vegetation based LCZ. Average LST for each LCZ increased from 1990 to 2020, which was attributed to background warming, while expansion of high LST areas was associated with LCZ transitions. Although average minimum temperature decreased, cool nights increased, warmest nights were unchanged and lowest minimum increased. Whereas highest minimum temperatures decreased, their trends were not statistically significant (p>0.05). Indices of daytime warming showed significant changes which included increase in average maximum temperature (p=0.002), increase in lowest maximum temperature (p=0), increase in number of very warm days (p=0.004) and decrease in number of cool days (p=0). The significant increase in daytime extremes was attributed to increase in highly absorbing LCZ as well as daytime pollution due to industrial activities. The study also concluded that development in water area or siltation of water bodies has more warming effect that other LCZ changes. The findings are important in showing that development needs to consider potential effects on the thermal environment and temperature extremes.